Functional role of endothelial CXCL16/CXCR6-platelet–leucocyte axis in angiotensin II-associated metabolic disorders. Issue 13 (23rd May 2018) - Collado, Aida; Marques, Patrice; Escudero, Paula; Rius, Cristina; Domingo, Elena; Martinez-Hervás, Sergio; Real, José T; Ascaso, Juan F; Piqueras, Laura; Sanz, Maria-Jesus
Abstract: Aims: Angiotensin-II (Ang-II) is the main effector peptide of the renin–angiotensin system (RAS) and promotes leucocyte adhesion to the stimulated endothelium. Because RAS activation and Ang-II signalling are implicated in metabolic syndrome (MS) and abdominal aortic aneurysm (AAA), we investigated the effect of Ang-II on CXCL16 arterial expression, the underlying mechanisms, and the functional role of the CXCL16/CXCR6 axis in these cardiometabolic disorders. Methods and results: Results from in vitro chamber assays revealed that CXCL16 neutralization significantly inhibited mononuclear leucocyte adhesion to arterial but not to venous endothelial cells. Flow cytometry and immunofluorescence studies confirmed that Ang-II induced enhanced endothelial CXCL16 expression, which was dependent on Nox5 up-regulation and subsequent RhoA/p38-MAPK/NFκB activation. Flow cytometry analysis further showed that MS patients had higher levels of platelet activation and a higher percentage of circulating CXCR6-expressing platelets, CXCR6-expressing-platelet-bound neutrophils, monocytes, and CD8 + lymphocytes than age-matched controls, leading to enhanced CXCR6/CXCL16-dependent adhesion to the dysfunctional (Ang-II- and TNFα-stimulated) arterial endothelium. Ang-II-challenged apolipoprotein E-deficient (apoE −/− ) mice had a higher incidence of AAA, macrophage, CD3 +, and CXCR6 + cell infiltration and neovascularization than unchallenged animals, which was accompanied by greater CCL2, CXCL16, and VEGF mRNA expression within the lesion together with elevated levels of circulating soluble CXCL16. Significant reductions in these parameters were found in animals co-treated with the AT1 receptor antagonist losartan or in apoE −/− mice lacking functional CXCR6 receptor (CXCR6 GFP/GFP ). Conclusion: CXCR6 expression on platelet-bound monocytes and CD8 + lymphocytes may constitute a new membrane-associated biomarker for adverse cardiovascular events. Moreover, pharmacological modulation of this axis may positively affect cardiovascular outcome in metabolic disorders linked to Ang-II.